PENINGKATAN KEPATUHAN PAJAK MELALUI DIGITALISASI: EFEKTIVITAS E-FILING DAN E-BILLING DI KPP PRATAMA SIDOARJO SELATAN - Rohmiatun, Erlyna Tri; Rosyida, Riska Ainur; Khoiroh, Fastabiqul (RISTANSI: Riset Akuntansi, 2025)
Digital transformation of taxation through the implementation of e-filing and e-billing has contributed to increasing tax compliance, reducing administrative burdens, and improving taxpayer experience at KPP Pratama Sidoarjo Selatan. This study uses a qualitative approach with a case study design and semi-structured interview techniques with individual taxpayers and MSMEs. The results show that ease of use of digital systems can increase compliance, but its effectiveness is influenced by the level of digital literacy, access to technology, and trust in system security. The main challenges include low digital literacy among elderly taxpayers, limited technical assistance, and system instability during peak reporting periods. This study emphasizes the importance of strengthening cybersecurity, increasing digital literacy, and integrating new technologies such as AI and blockchain to support an efficient, secure, and inclusive tax system.